Multi-trauma secondary to hypocalcaemia-induced seizure: A case report. (October 2016) - Shenouda, Rami; Carter, Sean; Wang, Kemble; Chow, Yvonne; Topliss, Duncan J.; Esser, Max P.
Abstract: Introduction: Fractures are known sequelae of seizures. We present a young male with bilateral acetabula and surgical neck of humerus (SNOH), right neck of femur (NOF) and thoracolumbar fractures in the context of a hypocalcaemic seizure secondary to severe malnutrition, secondary hyperparathyroidism and vitamin D deficiency. The authors believe that numerous severe injuries in a single patient secondary to seizure are extremely rare and have not been seen in the literature. Case report: A 25-year-old male presented to A&E following a collapse. He described limited movement and pain in all four limbs and collateral history described a generalised tonic–clonic seizure. XR and CT identified pelvic, femoral and humeral fractures, as well as compression fractures of T11, T12 and L1 vertebrae. His pelvic, femoral and SNOH fractures all required ORIF with intra-operative biopsy revealing abnormal bone quality. His spinal fractures did not require management. His young age and severe injuries prompted endocrinology and neurological evaluation. These revealed severe malnutrition secondary to behavioural and dietary factors with severe hypocalcaemia, secondary hyperparathyroidism and vitamin D deficiency. His metabolic and nutritional deficits were replaced intravenously and orally and his seizure attributed to hypocalcaemia. Discussion and conclusion: Clinical suspicion for fractures should be high as the rate of fracture following seizure is approximately 6% [1]. Close evaluation and tertiary survey should be completed as missed musculoskeletal injury has been reported to be over 10% [2] and pre-existing medical and social risk factors may increase the incidence of these injuries [3–4]. Given the young man's presentation, a high clinical suspicion was held for an underlying syndrome such as osteomalacia. Secondary to early aggressive treatment, a biopsy performed was non-diagnostic and features of osteomalacia were not present. Due to the potential consequences of a seizure, the authors recommend individuals who present with seizure or collapse be thoroughly examined and investigated to ensure no co-existing injury or pathology.